2011
DOI: 10.1097/hmr.0b013e318208cd1d
|View full text |Cite
|
Sign up to set email alerts
|

A case for safety leadership team training of hospital managers

Abstract: Team-based training that promotes specific learning-oriented leader behaviors can promote behavioral change among multidisciplinary groups of hospital managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Two53 54 of the twenty-six studies reviewed specifically evaluated an intervention designed to develop teamwork competencies among hospital leaders and administrators. Such programmes may differ from those focused on frontline providers in the level of emphasis on certain teamwork competencies (eg, transformational leadership, conflict management and mediation, broader internal and external environment awareness, boundary spanning activities that facilitate coordination with other internal or external teams, etc., may be of greater emphasis),55 56 as well as design (eg, greater use of table-top simulations or game-based approaches) 57…”
Section: Resultsmentioning
confidence: 99%
“…Two53 54 of the twenty-six studies reviewed specifically evaluated an intervention designed to develop teamwork competencies among hospital leaders and administrators. Such programmes may differ from those focused on frontline providers in the level of emphasis on certain teamwork competencies (eg, transformational leadership, conflict management and mediation, broader internal and external environment awareness, boundary spanning activities that facilitate coordination with other internal or external teams, etc., may be of greater emphasis),55 56 as well as design (eg, greater use of table-top simulations or game-based approaches) 57…”
Section: Resultsmentioning
confidence: 99%
“…Purpose, or team members sharing the same vision or goals for improving the organization (Singer et al, ), was identified in 26.5% ( N = 39) of the studies reviewed. Purpose can be represented by a vision statement (Trajkovski, Schmied, Vickers, & Jackson, ), meeting to achieve a common goal (Nes & Moen, ), or responding to a crisis (Müller‐Seitz & Macpherson, ).…”
Section: Resultsmentioning
confidence: 99%
“…To stimulate team adaptively by team-members is one of the (eight) essential key leadership skills (Anderson & McDaniel, Jr. 2000). If the program directors could shift their focus onto developing collaborative learning -and become more learning-oriented leaders -the teaching team would be better able as a team to anticipate external developments and the quality of the training of residents could be expected to improve (Singer et al 2011). …”
Section: Focus On Learningmentioning
confidence: 98%
“…Program directors who want to develop their leadership skills could focus greater attention within the teaching team on learning with and from one another (Singer et al 2011). Leadership skills can be learned; it is possible to learn how to resolve conflicts, to reinforce shared values and cooperative goals and to stimulate speaking up between team-members (Mitchell et al 2014).…”
Section: Practical Implicationsmentioning
confidence: 99%